Answer:
The correct option is;
y = 12·cos[π/2·(x- 2)] + 18
Explanation:
The general equation for the motion of a Ferris wheel as a function of time, t, can be presented as follows;
f(t) = A·cos(B·x + C) + D
Where;
A = The amplitude = Diameter/2 = 24/2 = 12 meters
The period = 4 minutes
B = 2·π/Period = 2·π/4 = π/2
D = The midline = 6 + 12 = 18 meters
Substituting the values gives;
f(x) = 12·cos(π/2·x + C) + 18
At x = 0, we have
f(x) = 6 = 12·cos(π/2×0 + C) + 18
cos( C) = (6 - 18)/12 = -1
∴ C = -π
We therefore have;
f(t) = y = 12·cos(π/2·t - π) + 18 = 12·cos[π/2·(x- 2)] + 18
y = 12·cos[π/2·(x- 2)] + 18.